Incubators Best Practices in Developed and Developing Countries: Qualitative Approaches - AL-MUBARAKI, Hanadi Mubarak; BUSLER, Michael; AL-AJMEI, Rashed; ARUNA, M. (Asian Journal of Empirical Research, 2013)
This paper aims to investigate and identify the best practices of incubators in developed and developing countries based on the incubators outcomes such as economic growth, fostering innovation and entrepreneurship. The study nature of this research is mainly qualitative approaches (multi-case studies, literature review). This investigation uses ten case studies, and the data was mainly collected by direct interview with four international incubator managers and organizational documents from the United States, Europe and other developing countries. The authors’ professional experiences on the topic provide the foundation for the paper. Results will provide incubators a roadmap for the development of new economies based on technology, as well as value added in technology transfer, innovation development, and an entrepreneurial climate. The finding of this research can help incubator managers, policy makers and government parties for successful implementation. Also, add new knowledge for academic literature incubators best practices in developed and developing countries. The authors believe that this paper has proven successful implementation of incubators in developed and developing countries and demonstrates a weight study to the current literature on incubator’s as a tool for economic growth, fostering innovation and entrepreneurship. Its beneficial outcomes provide useful information about developed and developing countries for both academicians and practitioners who are interested in incubators model.